Effects of NEAT1 levels on cardiovascular events and prognosis in diabetic nephropathy patients undergoing peritoneal dialysis: Role of NEAT1 in cardiovascular events - Liu, Mengjiang; Yan, Zhaodan; Zhang, Yi; Zhang, Shengli (Cellular and Molecular Biology, 2024)
The purpose of this study was to provide observational indicators for clinically predicting cardiovascular events in patients with diabetic nephropathy (DN) undergoing peritoneal dialysis by determining the effects of nuclear enriched abundant transcript 1 (NEAT1) levels on the cardiovascular events and prognosis in DN patients receiving continuous ambulatory peritoneal dialysis (CAPD). A retrospective analysis was conducted on the data of 80 DN patients undergoing CAPD. Patients were assigned to NEAT1 high expression group and NEAT1 low expression group. NEAT1 had a substantially increased expression in the serum of DN patients, and it could serve as a potential biomarker for predicting the development of DN. Patients with highly expressed NEAT1 had an higher level of high-sensitivity C-reactive protein (hs-CRP), larger cardiac structural parameters left ventricular end-diastolic diameter (LVED), left ventricular end-systolic diameter (LVESD), interventricular septal diameter (IVSD) and left ventricular posterior wall diameter (LVPWD), but a notably lower cardiac function evaluation indicator left ventricular ejection fraction (LVEF) than those with lowly expressed NEAT1. The coefficient (r) of correlation between NEAT1 and hs-CRP level was 0.3585 (P=0.0011). The incidence rates of acute myocardial infarction, congestive heart failure and angina in NEAT1 high expression group were higher than those in NEAT1 low expression group. Patients with NEAT1 high expression exhibited a higher mortality rate than NEAT1 low expression group. With the increase in NEAT1 levels, the level of hs-CRP rose in DN patients undergoing CAPD. A higher expression level of NEAT1 indicates poorer cardiac function, higher incidence rates of cardiovascular adverse events and a poorer prognosis in diabetics undergoing CAPD.